Amine Oxidation by Electrochemically Generated Peroxodicarbonate - Seitz, Ann-Katrin; van Lingen, Tim; Dyga, Marco; Kohlpaintner, Philipp J.; Waldvogel, Siegfried R.; Gooßen, Lukas J. (Synlett, 2022)
The N-oxidation of tertiary amines was achieved by using electrochemically generated peroxodicarbonate solutions as sustainable oxidizers. The presence of EDTA and 2,2,2-trifluoroacetophenone as a mediator was found to be crucial for converting water-insoluble substrates. Various tertiary amines were converted into their corresponding N-oxides in yields of up to 98%. The scope includes economically important surfactants and potential platform oxidizers.
Keywords: oxidation; peroxodicarbonate; boron-doped diamond; electrochemistry; amine oxides; organocatalysis